Obsidian in the Upper Palaeolithic of Iberia - Zilhão, João (2021)
Sourced from the Tyrrhenian Islands and exchanged over long distances, obsidian was used widely across prehistoric Western Europe. An obsidian core and bladelets from a newly discovered rockshelter site in south-eastern Spain, however, raised the possibility of an unrecognised mainland source of obsidian. EDXRF analysis of the Early Magdalenian finds from La Boja links them to a source 125km to the south-west. The artefacts were discarded during two brief activity phases at the site, indicating that obsidian procurement was integral to the technological choices of the site's users. The specificities of the technocomplex may explain the unique nature of this occurrence.